(untitled) - Jerome Laid Rosenberg (New York, 1980)
This book is designed to help the student of college chemistry by summarizing the chemical priciples of each topic and relating the solution of quantative problems to those fundamentals
Keywords: chemistry - outlines, syllabi, etc